Full-Wave Controlled Single-Phase AC Regulator: Design and Performance Analysis - Alfian Russifa Reza Asefi (Journal of Marine Electrical and Electronic Technology, 2024)
An alternating current (AC) regulator is a device designed to control the root mean square (RMS) output voltage for various applications. These include motor speed regulation, lamp dimming, temperature control for heating systems, and other power modulation tasks. The regulation of RMS voltage is achieved by adjusting the activation angle of the power switch, which in turn delays the output voltage waveform. This functionality categorizes the AC regulator as a phase delay control system. This study focuses on the design, implementation, and performance analysis of a single-phase full-wave AC regulator using a silicon-controlled rectifier (SCR). The research provides a detailed investigation into the waveform characteristics of current and voltage across varying load conditions, offering insights into efficiency, harmonic distortion, and operational stability. The findings are intended to advance the application of AC regulators in engineering fields, with a particular emphasis on improving reliability and energy efficiency in low and medium-power systems..